Waqf Funds for Higher Education in Malaysia and Bahrain: Drawing Lessons from the Experience - Sulaiman Haroon Yaqoob Arab; Habeebullah Zakariyah (Sekolah Tinggi Agama islam Negeri Majene, 2023)
Changes have been made to the concept of state-funded education that has been prevalent worldwide for millennia. Many unfavourable budget cuts, particularly during the economic downturn, created a challenging fiscal position for Higher Education Institutions (HEIs). As state financing declines, public institutions are under pressure to find new and creative methods to make ends meet. Public HEIs in Malaysia are obligated to gain their revenue due to the country's restrictive budget policies. Establishing waqf or an endowment fund at the higher education/university is viewed as an innovative step toward financial sustainability. This research compares and contrasts the waqf funding for higher education in Malaysia and the Kingdom of Bahrain and draws lessons for the latter. To accomplish this, the qualitative method is employed. The paper finds that several universities in Malaysia have initiated waqf centres as per the strategic plan of the Ministry of Higher Education. They have implemented a sophisticated online procedure and cutting-edge technologies for collecting monetary contributions via cash waqf and other means to achieve this goal. In contrast, the waqf fund has been used in the Kingdom of Bahrain for either elementary school education or specialized study. The higher education in the Kingdom of Bahrain lack supporting their students and faculty members through this fund. Based on the findings of this research, it is recommended that Bahrain's universities follow the lead of waqf-based universities to achieve autonomy.